Adherence to Growth Hormone Treatment in Children During the COVID-19 Pandemic - Erdal Eren; Semra Çetinkaya; Yasemin Denkboy Öngen; Ummahan Tercan; Şükran Darcan; Hande Turan; Murat Aydın; Fatma Yavuzyılmaz; Fatih Kilci; Beray Selver Eklioğlu; Nihal Hatipoğlu; Kübra Yüksek Acinikli; et al. (JCRPE, 2024)
INTRODUCTION: Treatment adherence is crucial for the success of growth hormone (GH) therapy. Reported non-adherence rates in GH treatment have varied widely. Several factors may have an impact on adherence. Apart from these factors, the global impact of the Coronavirus disease-2019 (COVID-19) pandemic, including problems with hospital admission and routine follow-up of patients using GH treatment, may have additionally affected the adherence rate. The primary objective of this study was to investigate adherence to treatment in patients receiving GH. In addition, potential problems with GH treatment during the pandemic were investigated. METHODS: This was a multicenter survey study that was sent to pediatric endocrinologists during the pandemic period (June-December 2021). Patient data, diagnosis, history of pituitary surgery, current GH doses, duration of GH therapy, the person administering therapy (either parent/patient), duration of missed doses, reasons for missed doses, as well as problems associated with GH therapy, missed dose data and the causes in the recent year (after the onset of the pandemic) were questioned. Treatment adherence was categorized based on missed dose rates over the past month (0 to 5%, full adherence; 5.1 to 10% moderate adherence; >10% non-adherence). RESULTS: The study cohort consisted of 427 cases (56.2% male) from thirteen centers. Median age of diagnosis was 8.13 (0.13-16) years. Treatment indications were isolated GH deficiency (61.4%), multiple pituitary hormone deficiency (14%), Turner syndrome (7.5%), idiopathic GH deficiency (7.5%), small for gestational age (2.8%), and “others“ (6.8%). GH therapy was administered by parents in 70% and by patients in 30%. Mean daily dose was 32.3 μg/kg, the annual growth rate was 1.15 standard deviation score (minimum -2.74, maximum 9.3). Overall GH adherence rate was good in 70.3%, moderate in 14.7%, and poor in 15% of the patients. The reasons for non-adherence were mainly due to forgetfulness, being tired, inability to access medication, and/or pen problems. It was noteworthy that there was a negative effect on adherence during the COVID-19 pandemic reported by 22% of patients and the main reasons given were problems obtaining an appointment, taking the medication, and anxiety about going to hospital. There was no difference between genders in the adherence rate. Non-adherence to GH treatment decreased significantly when the patient: administered the treatment; was older; had longer duration of treatment; and during the pandemic. There was a non-significant decrease in annual growth rate as non-adherence rate increased. DISCUSSION AND CONCLUSION: During the COVID-19 pandemic, the poor adherence rate was 15%, and duration of GH therapy and older age were important factors. There was a negative effect on adherence during the pandemic period.